Infrastruktur Transportasi Dalam Mendukung Pengembangan Objek Wisata Pantai Oyama di Desa Lokotoy, Kecamatan Banggai Utara, Kabupaten Banggai Laut - Dery Y. Lengkono; Kamran Aksa; Rimba Arief; Ariany Rofaidah (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study is to find out what transportation infrastructure has an influence and to find out what transportation infrastructure is the priority to be developed for the Oyama Beach Tourism Object in Lokotoy Village, North Banggai District, Banggai Laut Regency. This study uses quantitative methods and qualitative methods in responding to the needs of any supporting transportation infrastructure in supporting the development of the Oyama Beach Tourism Object in Lokotoy Village, North Banggai District, Banggai Laut Regency. Retrieval of data through observation, documentation, interviews, and questionnaires, where the sampling uses a proportional sample and purposive samples. The data obtained was then analyzed using the Borda Analysis tool. Of the 5 component indicators that show the most influence in supporting the development of the Oyama Beach Tourism Object, namely air transportation infrastructure where the availability of an airport at the research location makes many tourists come and visit.